Polypropylene and Polycarbonate containers have a varied effect on coagulation after haemodilution, as judged by TEG® in vitro - Roche, Anthony Michael (Department of Anaesthesia, 2017)
The reasons for this study were multi-factorial, but mostly due to some interesting data obtained from a pilot study conducted at University College London (UCL). In that study, the coagulation effects in vitro of two hetastarch solutions were compared with two crystalloids by means of thrombelastography (TEG®). The fluids compared were: 1. Hespan® (HES), a high molecular weight hetastarch (450kDa/O.7 substitution ratio) in a 0.9% saline solution - Laevosan, Austria. 2. Hextend® (HEX), also a high molecular weight hetastarch (670/0.75 substitution ratio) in a balanced electrolyte, lactate and glucose solution - BioTime Inc, Berkeley, California, USA. 3. Saline 0.9% 4. Hartmann's Solution (Ringer's Lactate) The crystalloids revealed no surprising differences known from previous published data, but data obtained from the hetastarch solutions revealed contradictory results to known in vivo results found in a phase III trial. This previous Phase III in vivo trial showed that HEX haemodilution produced a superior coagulation profile to HES, along with a significantly shorter r-time than HES. There was also a significantly smaller transfused volume of blood than HES in the HEX-treated patients. This Phase III study prompted the initial UCL in vitro haemodilution study mentioned above. In the UCL study, there were significantly impaired TEG® results, indicating severe hypocoagulability with HEX, when compared with HES. This included prolonged r-and k-times, as well as reduced a-angles and maximum amplitudes in the HEX group, compared with HES and crystalloid groups. Many theories were discussed for these controversial UCL results, but the thought was that a container-effect could have been responsible, as the in vitro UCL study methodology included the use of a polycarbonate container for initial storage, as well as for haemodilution of the blood in vitro. In view of the known wettable surface, as well as a strong negative surface charge of polycarbonate, it was suggested that the container surface itself could have affected coagulation. When different ionic compositions of the various fluids and starches were taken into account, it seemed possible that some interaction between the fluids and the material of the containers could have induced or inhibited coagulation at the container surface. The suspicion was that the observed change in TEG® variables was likely due to a methodologic idiosyncrasy. Previous track record of haemodilution and TEG research at the University of Cape Town made it an obvious setting for exploration of this problem. Preparations were thus made to test container effects with haemodilution in vitro at Prof MFM James' anaesthesia laboratory at the University of Cape Town. The hypothesis was that the use of polypropylene and polycarbonate containers, with their different chemical and surface properties, would lead to a variability in TEG® results obtained from fresh whole blood, as well as blood diluted with various fluid solutions. Choosing TEG® as a monitor of coagulation was essential, as it has a well-established track record in monitoring coagulation effects in trials of haemodilution (in vitro and in vivo). TEG® produces reliable and quick results, giving a reflection of global coagulation function. It, along with the Sonoclot®, are the only two devices which can reliably diagnose a hypercoagulable state. More will be mentioned on the TEG® later.